Implementasi Metode Basisdata Terdistribusi Untuk Pengelolaan Data Perpustakaan Berbasis Web - T M Zaini (Jurnal Informatika, 2010)
In order to achieve information about library collection and data access had a problem caused services still manually for locating that information or someone had to go by them self to the library, and also slowly processing transaction. By this problem, need to build application using distributed database methode to apply management information system based on web to handle library management. System can handle order transaction book collection, borrowing and returning, withdrawing and replacing lost books. Final Result  from this research is that the system can do accommodate that need by Management Information System based on web for  data management to implementation at library A and Library B (difference place). Keyword : Web, Barcode, Distributed Database